2013
DOI: 10.1099/jmm.0.046821-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mutations in the gyrA and gyrB genes and their association with the resistance of Mycobacterium tuberculosis to levofloxacin, moxifloxacin and gatifloxacin

Abstract: The purpose of the present study was to analyse mutations in the gyrA and gyrB genes of Mycobacterium tuberculosis and define the possible correlation between these mutations and resistance to levofloxacin (LVX), moxifloxacin (MFX) and gatifloxacin (GAT), based on their MICs. One hundred and forty-two M. tuberculosis clinical isolates were collected from pulmonary tuberculosis patients in the Moscow region. All M. tuberculosis strains were tested for drug susceptibility to rifampicin and isoniazid using the BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
29
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 24 publications
9
29
4
2
Order By: Relevance
“…The most common mutations in the gyrA gene that confer resistance in M. tuberculosis to fluoroquinolones are the A90V, S91P, and D94 (G, A, H, N, or Y) mutations (2,7,8,14,15). In this study, we found a rare mutation at codon 94 (D94V) in two isolates.…”
Section: Discussionmentioning
confidence: 56%
“…The most common mutations in the gyrA gene that confer resistance in M. tuberculosis to fluoroquinolones are the A90V, S91P, and D94 (G, A, H, N, or Y) mutations (2,7,8,14,15). In this study, we found a rare mutation at codon 94 (D94V) in two isolates.…”
Section: Discussionmentioning
confidence: 56%
“…The MIC was defined as the lowest concentration of antibiotic that reduced the viability of the culture by at least 90% as determined by fluorescence measurements at room temperature in top-reading mode, in which the excitation wavelength and emission wavelength were 530 nm and 590 nm, respectively. The MIC breakpoints were defined as 2 g/ml for OFX and LFX and 0.5 g/ml for MOX, GAT, and SPX (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…Cross-resistance exists between fluoroquinolones, and mutations that emerge under ofloxacin treatment are usually associated with moxifloxacin MICs above the WHO-defined critical concentration of 0.25 g/ml (4). However, 84 to 98% of isolates with mutations conferring fluoroquinolone resistance have MICs of Յ2 g/ml for moxifloxacin, which does not necessarily reflect clinical resistance (3,(5)(6)(7)(8)(9). Based on this, an alternative critical concentration of 2 g/ml has been suggested (5,6,10).…”
mentioning
confidence: 99%